Assessment of liver and renal function tests among gasoline exposed gas station workers in Mekelle city, Tigray region, Northern Ethiopia - Asefaw, Tsegay (PLoS One, 2020)
BACKGROUND: Volatile organic compounds such as gasoline and other fuels are associated with a wide variety of deleterious health effects including liver and kidney diseases. Gasoline station workers are exposed to a mixture of hydrocarbons during dispensing. However, no published studies investigated the liver and renal function tests of gasoline station workers in Ethiopia. Therefore the aim of this study was to assess liver and renal function tests among gasoline station workers. METHOD: A comparative cross sectional study was conduct from January 2018 to April 2018 at Mekelle city, Tigray region, Northern Ethiopia. Liver and renal function tests were analyzed on gasoline exposed (n = 43) and controls (n = 47) by Pentra C400 automated clinical chemistry analyzer. Student independent t-test and one way-ANOVA statistical methods were employed using SPSS Ver23. P-value < 0.05 was regarded as statistically significant. RESULT: The mean level of ALT, AST, Urea, creatinine, and uric acid was significantly higher among gasoline stations workers when compared to control study participants. There was also a significant increase in ALT, AST, Urea, creatinine and uric acid among gasoline stations with above 6 years exposure when compared with those exposed for ≤2 and3-6years. CONCLUSION: These findings suggest that increasing liver and renal parameters may be associated with exposure to gasoline and it is dependent on time of exposure to gasoline.